Jurassic geothermal landscapes and fossil ecosystems at San Agustín, Patagonia, Argentina - Guido, Diego Martín (2010)
An extensive, well-preserved, Late Jurassic (c. 150 Ma) geothermal system at San Agustín farm in the Deseado Massif, Patagonia, Argentina, is described. This deposit, along with others previously known from the same region, partially fills a considerable gap between Cenozoic and scattered Palaeozoic hot spring localities reported worldwide. The San Agustín deposit is novel because it represents a large (1.4 km2) and nearly complete geothermal landscape. Siliceous hot spring facies, both subaerial and subaqueous, are exposed side by side in their original spatial and geological context, set amongst intrusive rhyolite domes and fluviolacustrine sediments. The Jurassic hot springs have preserved an entire local ecosystem containing microbes, arthropods, gastropods and plants exhibiting Lagerstätten-style preservation. Plant preservation, in particular, ranges from decayed litter, to seedling sprouts, and to dense stands in life orientation with intact anatomy. The San Agustín deposit shares some ecological, taphonomic and sedimentological characteristics with modern hot springs. As it formed in a pre-angiosperm world, it is akin to the famous hot spring-related Devonian Rhynie cherts of Scotland. It differs in having excellent exposure, and thus will probably contribute to a better understanding of biosignal preservation in extreme environments in the geological record.